2002
DOI: 10.1097/00003246-200201000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an education program on decreasing catheter-related bloodstream infections in the surgical intensive care unit

Abstract: A focused intervention primarily directed at the ICU nursing staff can lead to a dramatic decrease in the incidence of primary bloodstream infections. Educational programs may lead to a substantial decrease in cost, morbidity, and mortality attributable to central venous catheterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
127
0
10

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 269 publications
(140 citation statements)
references
References 24 publications
3
127
0
10
Order By: Relevance
“…39 An educational program emphasizing important components of these guidelines successfully reduced catheterrelated BSIs in an ICU. 40 Of note, the authors of this study reported 9 Candida BSIs in the 18-month preintervention period (12% of all nosocomial BSIs in their ICU) and not a single episode of catheter-associated nosocomial candidemia during the 18 months after the educational program. 40 Third, the importance of antibiotic use as a risk factor for nosocomial candidemia suggests that control of antimicrobial use is an important component of candidemia prevention.…”
Section: This Issue Of Infection Control and Hospitalmentioning
confidence: 67%
See 1 more Smart Citation
“…39 An educational program emphasizing important components of these guidelines successfully reduced catheterrelated BSIs in an ICU. 40 Of note, the authors of this study reported 9 Candida BSIs in the 18-month preintervention period (12% of all nosocomial BSIs in their ICU) and not a single episode of catheter-associated nosocomial candidemia during the 18 months after the educational program. 40 Third, the importance of antibiotic use as a risk factor for nosocomial candidemia suggests that control of antimicrobial use is an important component of candidemia prevention.…”
Section: This Issue Of Infection Control and Hospitalmentioning
confidence: 67%
“…40 Of note, the authors of this study reported 9 Candida BSIs in the 18-month preintervention period (12% of all nosocomial BSIs in their ICU) and not a single episode of catheter-associated nosocomial candidemia during the 18 months after the educational program. 40 Third, the importance of antibiotic use as a risk factor for nosocomial candidemia suggests that control of antimicrobial use is an important component of candidemia prevention. These three strategies-improved hand hygiene, optimal catheter placement and care, and prudent antimicrobial use-should form the bedrock of our approach to prevent morbidity and mortality resulting from nosocomial candidemia.…”
Section: This Issue Of Infection Control and Hospitalmentioning
confidence: 67%
“…27 Unfortunately, there is a lack of published studies targeting improvement in CRBSI in PVC, with the majority of such interventions aimed only at central venous catheter insertion and maintenance. [28][29][30][31] Several recent studies have questioned current guidelines on the duration of PVC, reporting no conclusive benefit in routinely changing PVC after 72 hours. [32][33][34] However, present national guidelines recommend the removal or routine replacement of PVCs after 72 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown how hospital costs are significantly reduced with education on infection education [19,26,31,[36][37][38][39]. The costs of these educational interventions are small in comparison with the estimated savings [17][18][19]36].…”
Section: Discussionmentioning
confidence: 99%
“…Infection rates decreased from 4.9 to 2.1 cases per 1,000 catheter days. The effectiveness of a self-study module combined with posters, fact sheets and lectures has since been further demonstrated in the ICU setting, with several studies showing significant decreases in catheter-related bloodstream infection (CRBSI) [17,[26][27][28], VAP [18,29] and hand hygiene adherence [30].…”
Section: Critical Care Healthcare Workersmentioning
confidence: 99%